Dispositivo Electromecánico para accionamiento e Implementación de una Válvula de Control en Lazo Abierto para una Planta Térmica (2011)
A control valve is a system used to regulate the flow within a specific process. With this aim, a prototype of a control valve in open loop was designed, built and implemented, driven by an electromechanical device that fits the job specifications of a cooling system of the thermal plant located in the thermal plants laboratory UPB (Universidad Pontificia Bolivariana), with a didactic approach but wit application to real industrial equipment. The thermal plants laboratory of the UPB is equipped with a set of industrial equipment such as boiler-superheater steam-turbine-generator with a generating capacity of 5 KW. The positioning system and valve control is different from the conventionally available, since it is controlled by a LOGO! ®, 12/24 RC (PLC), which compares the external signal (opening position determined by the operator), with the internal signal. An electromechanical device for manipulation of the valve was developed, using the signals from two linear potentiometers installed in the mechanism. The accuracy in the positioning of the valve stem and the control of the opening is given by the speed ratio of the power transmission system that is part of the electromechanical device. With the tests performed on the prototype, a value Cv for the valve was obtained equal to 43.37, which when compared to the Cv of the valve’s manufacturer (49.42), a 12.2% acceptable deviation was observed.